Recent advances in the development of p21-activated kinase inhibitors - Coleman, Natalia (Landes Bioscience, 2012)
The p21-activated kinases (PAKs) are downstream effectors of the small G-proteins of the Rac and cdc42 family and have been implicated as essential for cell proliferation and survival. Recent studies have also demonstrated the promise of PAKs as therapeutic targets in various types of cancers. The PAKs are divided into two major groups (group I and II) based on sequence similarities. Although the different roles the PAK groups might play are not well understood, recent efforts have focused on the identification of kinase inhibitors that can discriminate between the two groups. In this review these efforts and newly identified inhibitors will be described and future directions discussed.